Infrared and microwaves at 5.8 GHz in a catalytic reactor - Séguin, Etienne; Thomas, Sébastien; Bazin, Philippe; Bond, Gary; Henriques, Carlos; Thibault-Starzyk, Frédéric (Physical chemistry chemical physics : PCCP, 2009)
An improved micro-reactor cell for IR spectroscopic studies of heterogeneous catalysis was built around a 5.8 GHz microwave cavity. The reactor can operate at 20 bars and with conventional heating up to 720 K, with reactant gas flows velocities (GHSV) from 25,000 to 50,000 h(-1). The temperature of the sample under microwave irradiation was measured by time resolved IR emission spectroscopy. The first experiment performed was the IR monitoring of the desorption of carbonates induced by irradiating an alumina sample by microwaves at 5.8 GHz.